2009
DOI: 10.1080/13102818.2009.10818405
|View full text |Cite
|
Sign up to set email alerts
|

Researches ConcerningIn VitroConservation of the Rare Plant SpeciesDianthus NardiformisJanka

Abstract: In our work, we studied the possibility to use in vitro methods for the preservation of the rare species from the Red List of Romanian Flora-Dianthus nardiformis Janka. The plant material (whole plants and seeds) was collected from 3 populations from Natura 2000 sites. The in vitro cultures starting from single node stem fragments had to face with high contamination degree with fungi. Despite this fact, using different methods of disinfection, culture media and combination of growth factors, aseptic tissues cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
(4 reference statements)
1
11
0
1
Order By: Relevance
“…The worst results in our experiment were achieved with sodium dichloroisocyanurate (DICA), with the biggest contamination of explants among all sterilizing agents used. Holobiuc et al (2009) reported that DICA also was the least efficient sterilizing agent for Dianthus nardiformis, comparing it with HgCl 2 , NaOCl and H 2 O 2 On the contrary, Osterc et al (2004) reported that reduction in contamination by using 16.6 g/L DICA for 15-min duration was very successful for vigorous cherry plants. Parkinson et al (1996) reported that sodium dichloroisocyanurate was more effective than commercially available bleach for disinfection.…”
Section: Resultsmentioning
confidence: 99%
“…The worst results in our experiment were achieved with sodium dichloroisocyanurate (DICA), with the biggest contamination of explants among all sterilizing agents used. Holobiuc et al (2009) reported that DICA also was the least efficient sterilizing agent for Dianthus nardiformis, comparing it with HgCl 2 , NaOCl and H 2 O 2 On the contrary, Osterc et al (2004) reported that reduction in contamination by using 16.6 g/L DICA for 15-min duration was very successful for vigorous cherry plants. Parkinson et al (1996) reported that sodium dichloroisocyanurate was more effective than commercially available bleach for disinfection.…”
Section: Resultsmentioning
confidence: 99%
“…ssp. simonkaianus (Péterfi) Tutin (Miclăuş et al, 2003), D. callizonus Schott & Kotschy (Holobiuc and Blindu, 2006), D. nardiformis Janka (Holobiuc et al, 2009(Holobiuc et al, , 2010a, D. pratensis M. Bieb. subsp.…”
Section: Introductionmentioning
confidence: 99%
“…simonkaianus (Miclăuş et al, 2003), D. glacialis subsp. gelidus (Cristea et al, 2006), D. nardiformis (Holobiuc et al, 2009), D. henteri (Cristea et al, 2010), and D. giganteus subsp. banaticus (Cristea et al, 2006;Jarda et al, 2011).…”
Section: In Vitro Multiplicationmentioning
confidence: 99%